Community college workforce preparation and career services: an exploration of efficacy from students’ perspectives - Smith, Amy Marie (Kansas State University, 2020)
Exploring the effectiveness of workforce development programming and services provided to students in community colleges in the United States is critical when considering the potential impact on community stakeholders and the economy. Not only is workforce development a part of the mission of community colleges, research indicates that obtaining gainful employment is one primary motivation for students’ participation in higher education. Further, labor market data show demand for a workforce that has postsecondary training in various industry sectors. However, there is limited research available that examines the employment readiness of students who have participated in workforce development programs and services offered by colleges within one of the nation’s largest community college systems, located in California. There is even less information available when examining this area through the perspective of students. Therefore, the purpose of this study was to explore the experiences and satisfaction of a sample of California community college students who are nearing completion of career technical education programs. Student participation in community college career services and their perceived attainment of critical employability skills is examined. Results of this study offer insights from students about community college career guidance services, usefulness of career service centers, and beliefs about their readiness to enter employment. Findings of this research suggest that while students believe they are prepared to enter the workforce, there is potential for community college workforce development programs to expand integrated and comprehensive employment preparation services to more effectively serve a greater number of students.
Keywords: Workforce development; Employment readiness; Community college